2001
DOI: 10.1152/ajpheart.2001.280.1.h22
|View full text |Cite
|
Sign up to set email alerts
|

Role of KATP + channels in regulation of systemic, pulmonary, and coronary vasomotor tone in exercising swine

Abstract: The role of ATP-sensitive K(+) (K(ATP)(+)) channels in vasomotor tone regulation during metabolic stimulation is incompletely understood. Consequently, we studied the contribution of K(ATP)(+) channels to vasomotor tone regulation in the systemic, pulmonary, and coronary vascular bed in nine treadmill-exercising swine. Exercise up to 85% of maximum heart rate increased body O(2) consumption fourfold, accommodated by a doubling of both cardiac output and body O(2) extraction. Mean aortic pressure was unchanged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 32 publications
11
59
2
Order By: Relevance
“…Excellent reproducibility of consecutive exercise trials has been reported previously (10,14,16,44). Four exercise protocols were performed on four different days and in random order.…”
Section: Exercise Protocolssupporting
confidence: 52%
“…Excellent reproducibility of consecutive exercise trials has been reported previously (10,14,16,44). Four exercise protocols were performed on four different days and in random order.…”
Section: Exercise Protocolssupporting
confidence: 52%
“…The contribution of 4-AP-sensitive K V channels to baseline coronary vascular resistance appears to be greater than that of other K ϩ channels investigated previously. Specifically, earlier studies found a ϳ10 -25% reduction in coronary blood flow following blockade of K ATP channels with glibenclamide (13,15,19,42) and little or no change in coronary flow following inhibition of BK Ca channels with iberiotoxin or charybdotoxin (30,36,40). We interpret these findings to indicate that vasodilator substances released by cardiac myocytes and endothelium under basal conditions regulate coronary microvascular resistance via pathways that converge largely upon K V channels.…”
Section: Discussionmentioning
confidence: 53%
“…Subsequently, animals were instrumented under sterile conditions as described previously. 17,18 Briefly, a thoracotomy was performed through the left fourth intercostal space. Subsequently, a polyvinylchloride catheter was inserted into the aortic arch, for the measurement of aortic pressure and blood sampling for the determination of PO 2 , PCO 2 , pH, O 2 saturation, and hemoglobin concentration (ABL800, Radiometer).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Excellent reproducibility of exercise trials has been reported previously. 17,18 After obtaining hemodynamic measurements with swine lying quietly on a treadmill, a 5-stage (1-5 km/h) treadmill exercise protocol was started with each exercise stage lasting 2 to 3 minutes. Hemodynamic variables were continuously recorded, and both arterial and mixed venous blood samples were collected during the last 60 s of each exercise stage for the determination of body oxygen consumption.…”
Section: Sunitinibmentioning
confidence: 99%